Association of Body Mass Index on Injuries and Outcomes After Ground-Level Falls. Issue 10 (October 2021) - Owattanapanich, Natthida; Schellenberg, Morgan; Switzer, Emily; Clark, Damon H.; Matsushima, Kazuhide; Inaba, Kenji
Background: The impact of body mass index (BMI) on trauma severity after ground-level falls (GLF) is currently unclear. This study aimed to examine the associations between BMI, injuries, and outcomes after GLF. Study Design: All patients ≥16 years of age injured by GLF were queried from the TQIP database (2013-2017). Exclusions were transfers, emergency department death, AIS 6 in any region, and missing data. Body mass index defined study groups: Underweight (BMI<18.5), Normal (BMI 18.5-24.9), Overweight (25.0-29.9), and Obese (≥30). Results: After exclusions, 131 570 patients remained for analysis. Most patients had a normal BMI (n = 58 503, 44%). Median ISS was 9 [IQR 9-10] in all groups. The Obese group had significantly lower rates of fractures than the Normal group, particularly femur fractures (53% vs. 64%, P < .001), but required orthopedic surgical intervention more frequently (45% vs. 41%, P < .001). On multivariate analysis, being overweight was protective against mortality (OR .881, P = .005), while obesity was not associated with mortality (OR 1.012, P = .821). Conclusion: Increasing BMI may be protective against both fracture risk and mortality after GLF. However, obese patients require operative fixation more frequently. Particularly as fracture diagnosis may be more challenging in the obese, special care should be taken during their tertiary surveys after GLF to ensure injuries are not missed.